2013
DOI: 10.5539/ies.v6n9p119
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Assessment for Learning Model for Elementary Classroom

Abstract: Assessment for Learning for elementary classroom is a concept that aims to stimulate self learning and development among the student via assessment model. This research aimed to 1) develop an Assessment for Learning Model for elementary classroom and 2) test and assess the outcome of our model. The authors utilized interviewing, questionnaire and assessment form as tools for data gathering. The data was analyzed by statistical methods, namely, mean and standard deviation. Lastly, we performed the t-test Depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Each student has a varied understanding according to their learning readiness, interests, and learning profile. Results of assessment become the basis for teachers to teach their students to new topics (Chueachot et al, 2013). Assessment has significant benefit if the teacher conducts an assessment before learning.…”
Section: Discussionmentioning
confidence: 99%
“…Each student has a varied understanding according to their learning readiness, interests, and learning profile. Results of assessment become the basis for teachers to teach their students to new topics (Chueachot et al, 2013). Assessment has significant benefit if the teacher conducts an assessment before learning.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers specifically examine AfL, which covers various issues such as the application of AfL in learning to write (Lee and Coniam, 2013), prerequisites for implementing AfL in learning (Heitink et al, 2016), teachers' views on AfL and databased decision making (Kippers et al, 2018), and a meta-analysis of Afl research in East Asian countries (Leong et al, 2018). Several studies reveal effective results related to the function of assessment as a natural companion in learning mathematics (Balan, 2010;Chueachot et al, 2013). This is in line with the results of Purnomo's research (2015), which found that there was an increase in the ability of elementary school students to solve math problems through an assessment design that had been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Įsivertinimu pagrįsto vertinimo modelio, integruoto į mokymosi veiklas, teigiamas poveikis mokinių pasiekimams įrodytas dirbant su V klasės pradinių klasių mokiniais (tyrime dalyvavo 107 mokiniai iš 3 klasių). Šio tyrimo autoriai pabrėžė, jog svarbu mokinius skatinti apmąstyti savo mokymosi tikslus ir jų siekti, dalyvauti vertinime ir mąstyti apie vertinimo kriterijus (Chueachot et al, 2013). Beje, patys mokytojai pripažįsta, jog jie nepakankamai gerai savo klasėse išnaudoja įsivertinimo teikiamas galimybes (Volante ir Beckett, 2011).…”
unclassified